The Effect of Printing Parameters on Scaffold Structure Using Low-cost 3D Printer - Sukindar, Nor Aiman; Awang Dahan, Azib Azhari; Abd Halim, Nor Farah Huda; Kamaruddin, Shafie; Sulaiman, Mohd Hafis (The Mattingley Publishing Co., Inc., 2020)
Additive Manufacturing (AM) technologies had widely used in most of the application such as aeronautics and automotive industries, for tooling and casting parts and even for medical purpose. These wide applications can be achieved by utilizing AM in the daily manufacturing process due to its capabilities to manufacture parts with complex shapes with no significant material removal process. In medical applications, the 3D printing method was used to fabricate bone support structure or known as scaffold structure. The ability of this technology in the fabrication of the scaffold structure lies by manipulating printing parameters to achieve desired porosity. This research investigated the effect of different porosity levels on a scaffold structure in terms of Equivalent Von-Mises Strain and Total Deformation. The porosity level was created by varying printing parameters including layer height, infill density, and shell thickness by slicing the initial solid CAD file using Repetier Host 3D printing software. The research mainly based on the Finite Element Analysis (FEA) in which the created scaffold structures were simulated to check its capability when different porosity on the design was applied. The simulation result indicates that the increase of porosity level will result in higher total deformation of the structure. Therefore, by manipulating the printing parameters, different levels of porosity structures can be achieved.